Is there any correlation between tumor infiltrating lymphocytes and expression of EGFR in squamous cell carcinoma of head and neck? A retrospective observational study - Senjuti Dasgupta; Nibedita Biswas; Asit Ranjan Deb; Sudipta Chakrabarti (Wolters Kluwer Medknow Publications, 2022)
Background: The dismal survival of one of the commonest malignancies of the world, head neck squamous cell carcinomas (HNSCC), has prompted researchers to probe into its various characteristics, especially those which reflect the outcome. Over the years, even though epidermal growth factor receptor (EGFR) and tumor-infiltrating lymphocytes (TIL) have emerged as useful biomarkers of the disease, the two parameters have rarely been considered in conjunction. Aims and Objectives: The study aimed to assess if there is any correlation between TIL levels (both stromal and intratumoral) and site, grade, stage, and EGFR score of HNSCC. Materials and Methods: A retrospective observational study was conducted in which histopathologically confirmed cases of HNSCC were included. The site of tumor, grade, stage, stromal and intratumoral TIL levels, and EGFR score were noted for each case. The data were analyzed using standard statistical tests. Results: The study population consisted of 122 patients with a mean age of 53.8 ± 9.2 years. The oral cavity was the commonest site of tumor (109 cases, 89.3%). Most cases were moderately differentiated (75, 61.5%). Pathological staging showed 66 cases (54%) to be in pT1, and 92 cases (75.4%) to be in pN0. In 68 cases (55.7%), stromal TIL level was high, and intratumoral TIL was low in 102 cases (83.6%). A statistically significant correlation was found between TIL levels and site, grade, pathological stage, and EGFR score of HNSCC. Conclusion: This pioneering study is unique in its exploration of the correlation between two significant biomarkers of HNSCC - TIL and EGFR score.